2021
DOI: 10.14719/pst.2021.8.4.1238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of blue light on the photosynthesis and flavonoid accumulation in leaves of Hedyotis corymbosa (L.) Lam.

Abstract: In plants, blue light with a short wavelength can promote light reaction in photosynthesis and increase dry mass. Photosynthesis plays an important role in supporting carbohydrates for primary and secondary metabolism processes. Flavonoids are phenolic compounds, a class of plant secondary metabolites, that can be obtained from many medicinal herbs. These phenolic compounds are involved in the reactive oxygen species scavenging system, inhibit lipid peroxidation by free-radical, chelate redox-active metals res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Blue LEDs, which have a short wavelength and a high energy light [ 36 ], played as a strong light environment condition that caused a decrease in the LHC amount and chlorophyll-b biosynthesis from chlorophyll-a through the enzyme chlorophyllide, an oxygenase [ 37 ]. A reduction in the chlorophyll-b content in the leaves of ex vitro plants grown under blue LEDs compared with a control was previously reported [ 27 , 28 ]. Plants that were exposed to a long-term red LED light (660 nm) treatment showed “red light syndrome”, which had a lower chlorophyll-a concentration in the leaves compared with the control in cucumbers and lettuce [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Blue LEDs, which have a short wavelength and a high energy light [ 36 ], played as a strong light environment condition that caused a decrease in the LHC amount and chlorophyll-b biosynthesis from chlorophyll-a through the enzyme chlorophyllide, an oxygenase [ 37 ]. A reduction in the chlorophyll-b content in the leaves of ex vitro plants grown under blue LEDs compared with a control was previously reported [ 27 , 28 ]. Plants that were exposed to a long-term red LED light (660 nm) treatment showed “red light syndrome”, which had a lower chlorophyll-a concentration in the leaves compared with the control in cucumbers and lettuce [ 12 , 31 ].…”
Section: Discussionmentioning
confidence: 65%
“…These molecules fuel the Calvin–Benson cycle for CO 2 fixation to produce carbohydrates and other assimilatory processes [ 42 ]. An increase in the photosynthetic product accumulation (such as sugar or starch) led to the rise of the fresh and dry weight of the leaf of H. corymbosa [ 27 , 28 ]. Plants grown under a high proportion of blue LEDs had greater F v /F m , Y(II), qP, and ETR values compared with the red LEDs, which correlated with a high biomass under those light treatments [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the study by Le et al (2021) showed that BL enhanced photosynthesis, likely by increasing stomatal conductance and the rate of photosynthetic electron transport [8]. Additionally, BL improved protection by decreasing the quantum yield of nonphotochemical loss.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the application of supplemental high-intensity blue light (HIBL) enhanced the contents of phenolic compounds, flavonoids in the leaves of Hedyotis corymbosa (L.) [8], and carotenoids such as violaxanthin and zeaxanthin involved in the process of dissipating absorbed energy into heat in Lactuca sativa [9]. Additionally, BL induces the synthesis of important pigments, Chls and β-carotene [5].…”
Section: Introductionmentioning
confidence: 99%